The Concept Of Love In Sufism - Bambang Suharto, Abdul Wachid (Jurnal Sastra Indonesia, 2022)
This research aimed to reveal and explain the concept of love in Sufism. In the perspective of Sufism, God's love precedes humans' love for their God because if God has loved them, as His servants, then they can never reject His love because that love comes first from God. Love in the tradition of Sufism is a great stage (maqamat) for the man to know and get closer to God. This research uses qualitative research approach. This approach serves to interpret, express, and explain the concept of Sufism about love. It is library research, with the primary data source is the work of the Sufi-poets like Jalaluddin Rumi and Imam Al-Ghazali. The results of this research used Al-Ghazali’s notion of love which is: 1) self-love, 2) love caused by the advantages derived from the object of the beloved, 3) love caused by goodness and beauty, 4) love inspired by kindness and beauty in moral meaning, 5) love born because of munaasabah or secret affinity.